BULAN SURA DALAM PERSPEKTIF ISLAM - Partin Nurdiani (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This article reveals the Sura the rituals of Javanese society in Suramonth. They believe that it is Tundan dhemit, a time when there was agroup of ghosts who are looking for prey, especially those who are unawareand careless. The people serve this ceremony to protect themselvesfrom this disaster. Meanwhile In Islam Sura or Muharram is the specialmonth because there were many histories about prophets and their struggle.This phenomenon results a controverse which arouse to sin.